Experimental Investigation of Reinforced Concrete Column Embedded with the Angle Steel Shapes. (2015) - Lisantono, Ade; Budiman, Agung; Sidauruk, Paulinus Haesler Boantua
Abstract: Column is an important structural element in a building, because it carries some loads from the beams and the floors connecting to the column. Sometimes it needs to strengthen the existing column for some reasons. For example the load capacity of the column must be increased due to the compressive strength of the concrete column does not comply with the specified requirement. Investigation of the reinforced concrete column with angle steel shapes embedded at the corner of the column is limited. Therefore, it needs to investigate before developing the analysis for practical purpose design. This research conducts the experimental program of the reinforced concrete column with equal-leg angle steel shapes embedded at corner of the column. Eight specimens were tested in this experimental program. Four columns were subjected to the concentrically load and the others were subjected to eccentrically load. The specimens which embedded with angle steel shapes have various stiffeners spacing of 50 mm; 100 mm, and 150 mm. The column has length of 750 mm with sectional dimension of (75 mm x 75 mm). The column has four longitudinal reinforcements of 8 mm and stirrup of 5 mm. The equal-leg angle steel shape has size of (22.1 mm x 22.1 mm x 2 mm). The results of the experimental program show that compare to the reference specimen, the increment load of concentrically loaded column embedded with angle steel shape with stiffener spacing 50 mm, 100 mm, and 150 mm were 210.4447%, 235.5426%, and 185.6640%, respectively. While the increment load of eccentrically loaded column embedded with angle steel shape with stiffener spacing 50 mm, 100 mm, and 150 mm were 85.5607%, 34.6697%, and 42.9479%, respectively